The Impact of YouTube Advertising on Consumer Purchase Behavior: A Study of Guwahati’s Market - Singh, Nidhi; Panda, Khirod Chandra (Journal of Global Economy, Business and Finance, 2025)
The importance of consumers' opinions toward social media advertising, particularly on platforms like YouTube, has received a lot of attention recently. In today's digital scene, YouTube is one of the most beloved social networking platforms. This study explores into the critical interaction between YouTube views and the ads that are shown, with the goal of illuminating its impact on consumer buying behavior. To achieve this goal, an online questionnaire was widely distributed among Guwahati residents via various social media outlets. This study aims to assess the effectiveness of YouTube advertisements by investigating their impact on actual consumer purchase behavior. The length of the commercial, its presentation, and audience engagement levels are all important considerations. This study aims to shed light on the critical role that YouTube views play in affecting consumer choices, eventually giving vital data for advertisers and marketers looking to capitalize on the power of social media advertising in the digital era.